Pengaruh Produk, Pelayanan, dan Religiusitas Terhadap Keputusan Nasabah Menggunakan Jasa Bank Syariah Indonesia - Naufal Farras Kamil; Handry Sudiartha Athar (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of Product, Service, and Religiosity variables on Customer Decisions to Use Indonesian Islamic Banking Services. In this study, 100 respondents located in Mataram City were used as samples. Based on the results of data analysis, it can be concluded that the Product and Service variables have a positive and significant effect, while the Religiosity variable does not have a positive and significant effect on Customer Decisions to Use Islamic Banking Services Indonesia. The Product variable has a positive and significant effect on Customer Decisions to Use Islamic Banking Services Indonesia, as evidenced by H0 being rejected and H1 being accepted. The Service variable has an effect on Customer Decisions to Use Islamic Banking Services Indonesia, as evidenced by H0 being rejected and H2 being accepted. The Religiosity variable does not have a significant effect on Customer Decisions to Use Islamic Banking Services Indonesia, as evidenced by H0 being accepted and H3 being rejected.